One-year myopia control efficacy of spectacle lenses with aspherical lenslets - Bao, Jinhua; Yang, Adeline; Huang, Yingying; Li, Xue; Pan, Yiguo; Ding, Chenglu; Lim, Ee Woon; Zheng, Jingwei; Spiegel, Daniel P; Drobe, Björn; Lu, Fan; Chen, Hao (British journal of ophthalmology, 2022)
AimsTo evaluate the 1-year efficacy of two new myopia control spectacle lenses with lenslets of different asphericity.MethodsOne hundred seventy schoolchildren aged 8–13 years with myopia of −0.75 D to −4.75 D were randomised to receive spectacle lenses with highly aspherical lenslets (HAL), spectacle lenses with slightly aspherical lenslets (SAL), or single-vision spectacle lenses (SVL). Cycloplegic autorefraction (spherical equivalent refraction (SER)), axial length (AL) and best-corrected visual acuity (BCVA) were measured at baseline and 6-month intervals. Adaptation and compliance questionnaires were administered during all visits.ResultsAfter 1 year, the mean changes in the SER (±SE) and AL (±SE) in the SVL group were −0.81±0.06 D and 0.36±0.02 mm. Compared with SVL, the myopia control efficacy measured using SER was 67% (difference of 0.53 D) for HAL and 41% (difference of 0.33 D) for SAL, and the efficacy measured using AL was 64% (difference of 0.23 mm) for HAL and 31% (difference of 0.11 mm) for SAL (all p<0.01). HAL resulted in significantly greater myopia control than SAL for SER (difference of 0.21 D, p<0.001) and AL (difference of 0.12 mm, p<0.001). The mean BCVA (−0.01±0.1 logMAR, p=0.22) and mean daily wearing time (13.2±2.6 hours, p=0.26) were similar among the three groups. All groups adapted to their lenses with no reported adverse events, complaints or discomfort.ConclusionsSpectacle lenses with aspherical lenslets effectively slow myopia progression and axial elongation compared with SVL. Myopia control efficacy increased with lenslet asphericity.Trial registration numberChiCTR1800017683.